Dietary supplement use in high-intensity functional training (HIFT) athletes by competition level - Jack Livingston; Sofea Smith; Kworweinski Lafontant; Claudia Gonzalez; Michelle Da Silva Barbera; Linh Nguyen; Susan Kampiyil; Jeffrey R. Stout; David H. Fukuda (Journal of the International Society of Sports Nutrition)
Background Dietary supplements (DS) are used by athletes to aid sport-specific performance and recovery. High Intensity Functional Training (HIFT) is a unique sport with muscular strength/power/endurance, aerobic endurance, and rehydration concerns. While a multitude of DS may be beneficial for HIFT athletes, yet usage patterns unclear.Methods Forty-nine HIFT athletes (24 women, 25 men; Age = 37.8 ± 10.5 years; BMI = 25.7 ± 3.7 kg/m2) completed a supervised Qualtrics cross-sectional survey. Regarding competition level (CL), Athletes were classified as noncompetitive, local, regional, or national based on previous HIFT competition experience. Participants reported DS use and provided open-ended rationales for use or discontinuance. Data are presented descriptively; no inferential statistics were conducted due to low sample sizes between CLs. Two coders performed inductive thematic analysis via consensus to reveal initial codes and final themes.Results The distribution of CL were: noncompetitive = 12 (25%), local = 30 (61%), regional = 4 (8%), national = 3 (6%). Most participants reported using DS (n = 46, 94%) with caffeine (n = 35, 76%) and electrolyte drinks (n = 35, 76%) as the most favored supplements. Whey/casein protein (n = 33, 72%), creatine (n = 32, 70%), and multi-vitamins (n = 22, 48%) rounded out the top five DS. These were similar among all CL, except for magnesium and multi-vitamins being used among all three national-level athletes. Prevalent reasons for using DS were general health (n = 23, 50%), recovery optimization (n = 19, 41%), and rehydration (n = 13, 28%). Half of the athletes (n = 23) had discontinued at least one supplement, chiefly because of lifestyle changes (n = 7, 30%), perceived lack of benefit (n = 7, 30%), or cost (n = 3, 13%); adverse effects were rarely the reason for discontinuation (n = 1, 4%).Conclusions Across competition tiers, HIFT athletes most commonly rely on caffeine, electrolyte drinks, creatine, dairy-based protein, and multivitamins. While we were limited by a small sample size, the varying motives for DS use suggest that practitioners should assess the rationale behind DS use for HIFT athletes before providing evidence-based advice.